The Argument for Academic Engagement with China - Kirby, William (International Higher Education, 2023)
In education as in other areas, the US and Chinese governments privilege self-interest over shared concerns. Mutual paranoia takes precedence over reciprocal benefit. This places at risk the robust—and successful—collaboration between Chinese and US universities, which has been a powerfully positive force for both countries. Now is the time to remain engaged—indeed to deepen our engagement with our Chinese partners, for history tells us the perils of academic self-isolation.